Advances in Intelligent Informatics, Smart Technology and Natural Language Processing Selected Revised Papers from the Joint International Symposium on Artificial Intelligence and Natural Language Processing (iSAI-NLP 2017) - Theeramunkong, Thanaruk; Kongkachandra, Rachada; Ketcham, Mahasak; Hnoohom, Narit; Songmuang, Pokpong; Supnithi, Thepchai; Hashimoto, Kiyota (Advances in Intelligent Systems and Computing,, 2019)
This book constitutes the refereed proceedings of the 13th Joint International Symposium on Artificial Intelligence and Natural Language Processing, iSAI-NLP2017, held in Prachuap Khiri Khan, Thailand, in August 2017, and the 10th International Conference on Knowledge, Information and Creativity Support Systems, KICSS2015, held in Phuket, Thailand, in November 2015. It presents 22 carefully reviewed full papers on the following topics: artificial intelligence; machine learning; decision support systems; data mining; data analysis; natural language processing; multilingual processing; language and ontology unification; text classification; knowledge-based information systems; tracking systems; virtual reality; pattern recognition and image processing; signal classification; object detection and recognition; real-time sensor network; cloud-based services; and information security.